Companionship in labour: Do the personality characteristics of labour supporters influence their effectiveness - B. Chalmers; W. L. Wolman; V. C. Nikodem; A. M. Gulmezoglu; G. J. Hofmeyer (AOSIS, 1995)
Recent research has revealed beneficial post-partum, psychosocial effects on the mother following labour which was accompanied by supportive companions. Whether these effects are obtained as a result of having companionship during labour or because of specific personality characteristics of the companions provided is important and is explored in this paper. Although findings revealed few differences in adjustment between women who were supported by different companions, some variability in the post-partum state anxiety and depression scores were noted which suggest that selection of an appropriate supporter is an important aspect of such programmes.